Designing The English Argumentative Essay Writing Test Based on Critical Thinking Skills - Moh. Yamin; Slamet Setiawan; Syafi'ul Anam (VELES Voices of English Language Education Society, 2023)
Designing the argumentative essay test instrument based on critical thinking skills is the step to produce the writing test instrument used for measuring the students’ performance in writing the argumentative essay with critical thinking skills. This study aimed at measuring the validity and reliability of the argumentative essay writing instrument test with critical thinking skills. The procedure to create the writing test instrument credible was conducted by testing the instrument valid and reliable. The process of validating is through content validity and expert validation. The process of making the instrument reliable was done by checking the score of the students tested in trying out. The result of validating and making the instrument reliable was stated effective for use to get the data collection. Either pretest or posttest of the instrument in each component is stated reliable and it affirms the reliability of the instrument. The notes from the validator of the instrument are in line with the statistics stating that the instrument can be used for collecting the data. As a result, the writing test instrument was ready to use for the research. It is suggested that this instrument can be used for other relevant issues and studied more deeply for the next relevant studies.